1989
DOI: 10.1172/jci114108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and histologic localization of human growth hormone-variant gene expression in the placenta.

Abstract: The human growth hormone-variant (hGH-V) gene is one of five highly similar growth hormone-related genes clustered on the short arm of chromosome 17. Although the pattern of expression of the adjacent normal growth hormone (hGH-N) and chorionic somatomammotropin (hCS) genes in this cluster are well characterized, the expression of the hGH-V gene remains to be defined. In previous studies, we have demonstrated that the hGH-V gene is transcribed in the term placenta and expressed as two alternatively spliced mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Placental GH is produced by the syncytiotrophoblast in vivo (8,9) and in vitro (lo), and we recently have demonstrated that this hormone is involved in autocrine mechanism in the syncytiotrophoblast (1 I).…”
Section: Abstracxmentioning
confidence: 99%
“…Placental GH is produced by the syncytiotrophoblast in vivo (8,9) and in vitro (lo), and we recently have demonstrated that this hormone is involved in autocrine mechanism in the syncytiotrophoblast (1 I).…”
Section: Abstracxmentioning
confidence: 99%
“…The hGH-N gene is expressed in the somatotrope and lactosomatotrope cells of the anterior pituitary, whereas the remaining four genes-hCS-L, hCS-A, hGH-V, and hCS-B-are expressed in the syncytiotrophoblastic layer of the placenta (5,6). hGH-N, hCS-A, and hCS-B are expressed at very high levels, constituting 2-3% of total mRNA in their respective tissues.…”
mentioning
confidence: 99%
“…The presence of this hormone in the syncytiotrophoblast was confirmed with immunohistochemical methods [6]. Besides, with molecular methods GH-V gene expression was shown in the placenta, and no expression of the GH-N gene, responsible for GH1 production, was demonstrated [7,11,12]. Moreover, the presence of PGH receptors was detected in the placenta, and this suggests a direct influence of PGH on placenta function through auto-and paracrine mechanisms, …”
Section: Discussionmentioning
confidence: 83%